A system wide approach for infrastructure resilience technical note. (Metro Manila, Philippines Asian Development Bank, 2020)
Climate change is affecting infrastructure investments worldwide, leading to asset value losses, higher operating costs, and reduced economic benefits. Co published by ADB and the Global Center on Adaptation, this technical note emphasizes that the evaluation of climate related financial risks need to be broadened to include the planning, delivery, and management of national infrastructure plans. It was produced as an input to the Global Commission on Adaptation Climate Adaptation Summit 2021.
Keywords: Climatic changes -- Government policy; Finance sector development; Climatic changes -- Cost effectiveness; Electronic books